Selective conformational control by excitation of NH imino vibrational antennas - Góbi, Sándor (2019)
An imino group was used for the first time as a vibrational antenna to manipulate molecular conformations. Imino-thiol isomers of thioacetamide were generated upon UV-irradiation of its amino-thione tautomer isolated in argon matrices at 11 K. Selective and reversible conformational isomerizations were induced by narrowband near-IR irradiation tuned at the frequencies of the 2ν(NH) first stretching overtone of each imino-thiol isomer. The conformational isomerization concerns the change in the orientation of a remote -SH group, while the orientation of the imino (C[double bond, length as m-dash]NH) group remains the same. Supported by quantum chemical anharmonic computations, this allowed for a reliable, isomer-selective vibrational assignment of the four imino-thiol isomers extending now over the full mid-IR and near-IR ranges. It was found that the experimental IR intensities of the 2ν(NH) first stretching overtones (computed 4-5 km mol-1) of the imino-thiol forms are comparable to those of the ν(NH) stretching fundamentals (computed 2-4 km mol-1). This is the first time such a phenomenon is reported for an imine molecule. The kinetics of conformational isomerization was monitored in situ, indicating that the irradiation-induced processes are significantly faster than the tunneling-driven spontaneous cis-trans rotamerization of the -SH group. Quantum yields for the rotamerizations of the -SH group resulting from the vibrational excitation of a remote -NH group were estimated and found to be comparable to those observed for matrix-isolated carboxylic acids and amino acids, where conformational changes of the -OH group were induced by the direct vibrational excitation of 2ν(OH) first stretching overtones.